Enhanced Recovery after Vascular Surgery - Stojanovic, Milena D.; Markovic, Danica Z.; Vukovic, Anita Z.; Dinic, Vesna D.; Nikolic, Aleksandar N.; Maricic, Tijana G.; Janković, Radmilo J. (Frontiers in Medicine, 2018)
The beginnings of the Enhanced Recovery After Surgery (ERAS) program were first developed for patients in colorectal surgery, and after it was established as the standard of care in this surgical field, it began to be applied in many others surgical areas. This is multimodal, evidence-based approach program and includes simultaneous optimization of preoperative status of patients, adequate selection of surgical procedure and postoperative management. The aim of this program is to reduce complications, the length of hospital stay and to improve the patients outcome. Over the past decades, special attention was directed to the postoperative management in vascular surgery, especially after major vascular surgery because of the great risk of multiorgan failure, such as: respiratory failure, myocardial infarction, hemodynamic instability, coagulopathy, renal failure, neurological disorders and intra-abdominal complications. Although a lot of effort was put into it, there is no unique acceptable program for ERAS in this surgical field, and there is still a need to point out the factors responsible for postoperative outcomes of these patients. So far, it is known that special attention should be paid to already existing diseases, type and the duration of the surgical intervention, hemodynamic and fluid management, nutrition, pain management and early mobilisation of patients.